Focusing On Mistakes: Pragmatically Implementing Growth Mindset - Zach Patterson (Canadian Society for Studies in Education, 2022)
As an early career educator looking for new and innovative ways to reform educational practice, I discovered the theory of Growth Mindset. Growth Mindset research has shown that interventions focused on neuroplasticity and the malleability of intelligence can have academic and behavioural benefits in classrooms where implemented. Missing from this research are practical classroom activities that can be used regularly to continue to promote a growth mindset in students. This paper critically examines the tenets of Growth Mindset and its merits, including the importance of error culture in a classroom. Based on this exploration, a suggested series of questions for an error correction task design are given, including implications of implementation.